Visit to a shelf: the Paiteño meeting of Manuela Sáenz and Ricardo Palma - Adriazola Silva, Juan Carlos (2019)
The way in which two prominent figures in the history of Peru and Ecuador, Manuela Sáenz Aizpuru and Ricardo Palma Soriano, became related is a transcendental matter that cannot go unnoticed in the exhaustive study of the work of Palma. It seems that it all began with a simple and curious courtesy visit that he made to that wasteland in her poor house in the Piuran port of Paita in 1856. This meeting would serve especially to Palma as a pretext for the creation of some flavorous traditions in which he made known various aspects of the genius and figure of the one who was considered an outstanding patriotic woman in Peru during the period of Independence of San Martín; and later, a celebrity often loathed forbeing the favorite of the Liberator Simón Bolívar. The life of this woman is intense and is marked since childhood by the harshness of the disaffects, which turned her into a rebellious and determined young woman who would not fear anything or anyone in the future. As she entered maturity, however, she came to know the luxury, glamour and glory that come with power. When his beloved hero died, the revenge of Bolivar’s enemies caught up with her. This resulted in a prolonged political exile, aggravated by abandonment, illness and poverty. Its vital trajectory makes it worthy of adorning the gallery of significant women of Hispanic American history that go beyond the first half of the nineteenth century.